Multi-wavelength picosecond BaWO4 Raman laser with long and short Raman shifts and 12-fold pulse shortening down to 3 ps at 1227 nm. (3rd January 2018) - Frank, M; Jelínek, M; Vyhlídal, D; Kubeček, V; Ivleva, L I; Zverev, P G; Smetanin, S N
Abstract: In this paper, we demonstrate the generation of three (1179, 1227, and 1323 nm) Stokes components of stimulated Raman scattering with long (925 c m − 1 ) and short (332 c m − 1 ) Raman shifts in an all-solid-state, synchronously pumped, extra-cavity Raman laser based on a BaWO4 crystal excited by a quasi-continuous, 36 ps, diode side-pumped Nd:GdVO4 laser generating at the wavelength of 1063 nm. We achieved the strongest 12-fold pulse shortening down to 3 ps at the 925 c m − 1   +  332 c m − 1 shifted 1227 nm wavelength due to a shorter dephasing time (wider linewidth) of the short-shift 332 c m − 1 Raman line, resulting in a peak power of 2.5 kW.